Association between retinal arterial narrowing and left ventricular diastolic dysfunction in masked hypertensives. Issue 6 (19th May 2020) - Huang, Huiling; Cao, Yalin; Li, Jiayong; Liu, Chen; Owusu‐Agyeman, Marvin; Chen, Baolin; Li, Ling; Du, Fawang; Hu, Xingwei; Liu, Yanqiu; Ye, Min; Dong, Bin; et al.
Abstract: Morphological change in retinal vessel diameters has been reported to be associated with negative cardiovascular outcomes, but its association with left ventricular diastolic dysfunction (LVDD) is not clear. This study aimed to examine the association between echocardiographic markers of LVDD and retinal vascular diameters, in untreated masked hypertension (MH). In this observational study, 105 MH patients without other cardiovascular risks were included (mean age 48.4 ± 5.7, female 72.4%). All individuals underwent extensive clinical and laboratory investigations, including echocardiography, ambulatory blood pressure monitoring, and retinal vascular diameters measured by optical coherence tomography. In the group, LVDD was diagnosed in 36 participants evaluated by left ventricular volume index, E/A and E/e' ratio. Compared to non‐LVDD, LVDD subjects displayed narrower retinal arteriolar diameter (139.1 ± 33.8 vs 165.1 ± 29.1; adjusted P = .007) and wider retinal venular diameter (237.9 ± 42.2 vs 214.9 ± 44.8; adjusted P = .045). Significant and independent associations were demonstrated for retinal arteriolar narrowing and E/A ratio (adjusted β = 0.744, P = .031) and for retinal arteriolar diameter and E/e' ratio (adjusted β = −0.158, P = .001) after controlling for age, gender, body mass index, ambulatory systolic blood pressure, low‐density lipoprotein cholesterol, and retinal venular diameter. In untreated MH subjects, retinal arteriolar diameter, a marker of microvascular damage, was independently associated with echocardiographic markers of diastolic dysfunction. These findings might underscore the hypothesis that microvascular disease could contribute to cardiac remodeling.